2020
DOI: 10.4081/ejh.2020.3119
|View full text |Cite
|
Sign up to set email alerts
|

Ozone at low concentrations does not affect motility and proliferation of cancer cells in vitro

Abstract: Exposure to low ozone concentrations is used in medicine as an adjuvant/complementary treatment for a variety of diseases. The therapeutic potential of low ozone concentrations relies on their capability to increase the nuclear translocation of the Nuclear factor erythroid 2-related factor 2 (Nrf2), thus inducing the transcription of Antioxidant Response Elements (ARE)-driven genes and, through a cascade of events, a general cytoprotective response. However, based on the controversial role of Nrf2 in cancer in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
(54 reference statements)
2
6
0
Order By: Relevance
“…It is worth noting that small local changes in the amount of reactive oxygen species (ROS), as induced by mild ozonation [ 15 ], may stimulate the polymerization of cytoskeletal actin [ 29 , 30 , 31 ] that is essential to form cell protrusions and promote adhesion [ 32 , 33 ]. However, the wound healing assay showed that the O 3 -induced increase in the surface processes was not paralleled by a higher migration rate, consistent with previous evidence that O 3 exposure does not affect the cell migration capability [ 34 ].…”
Section: Discussionsupporting
confidence: 86%
“…It is worth noting that small local changes in the amount of reactive oxygen species (ROS), as induced by mild ozonation [ 15 ], may stimulate the polymerization of cytoskeletal actin [ 29 , 30 , 31 ] that is essential to form cell protrusions and promote adhesion [ 32 , 33 ]. However, the wound healing assay showed that the O 3 -induced increase in the surface processes was not paralleled by a higher migration rate, consistent with previous evidence that O 3 exposure does not affect the cell migration capability [ 34 ].…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, gas exposure did not affect proliferation in both LPS‐activated and LPS + DMF cells, as shown by the evaluation of both the mitotic index and BrdU‐positivity, according to previous reports on other cell types in vitro (Costanzo et al, 2020 ; Costanzo et al, 2015 ; Scassellati et al, 2017 ).…”
Section: Discussionsupporting
confidence: 82%
“…The contrary can occur in cancer cells whereby a high cellular antioxidant status protects the cell from ROS leading to an increased cancer cell survival and a resistance to chemotherapy [20]. In dependence on the ozone concentrations, this effect has been explored by Costanzo and colleagues with the result that there is no effect on the motility and proliferation of cancer cells in vitro in the systemically used concentrations following the low-dose ozone concept [21,22].…”
Section: Signal Transduction and Bioregulation The Role Of Glutathionementioning
confidence: 99%